Covid-19 integrated data governance UiTM 1.0: CoiNDAG UiTM 1.0 / Mohammad Azuwadi Mohd Yasin, Yarina Ahmad and Marni Ghazali - Mohd Yasin, Mohammad Azuwadi; Ahmad, Yarina; Ghazali, Marni (2021)
This innovative design demonstrates the importance of data and information for decision-making by creating databases integrated with the application engine to improve accessibility to the essential data and information related explicitly to Covid-19 and enhance value-added operation activity during pandemics. Moreover, based on a survey related to the effectiveness of CoiNDAG UiTM 1.0, 68.7% of respondents were strongly satisfied and 31.3% were satisfied with CoiNDAG UiTM 1.0.